On childhood and philosophy: suspension, profanation, and attention in training experience - Oliveira, Alice Pessanha Souza de; Teperino, Juliana Braga; Sales, Luiz Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article aims at analyzing our own experience as students from the undergraduate and postgraduate program in training in working with children and philosophy. For that purpose, we will address the training experience carried out by the Philosophy and Children Studies Group between 2017 and 2018. This text proposes a reflection on the extent to which training experience is not only a training course in philosophy with children, but also a school time capable of modifying our relationship with knowledge. In this way, we propose to make a course description: its development, the organization of the groups, its dynamics, and its methodology.Thus, we will work on the concept of childhood, which was proposed for our group in 2017. Lastly, we will analyze Masschelein’s and Simons’ works in order to reflect on three school elements: attention, profanation, and suspension. We will study how these elements were manifested in training experience and how they influenced the transformation of our relationship with knowledge.